Mengulik Makna Konsep Penebusan dalam Kitab RUT - Yakup Hariyanto (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
Ruth's life is a depiction of a devout and faithful person. Her simple and obedient life has transformed all aspects of her life. The form of love that Ruth showed to Naomi has opened a great opportunity for Ruth to experience an encounter with Boaz. The bitterness of her life did not make her spirit run aground and disappear. Ruth experienced redemption carried out by Boaz. The expression go'el, which means redemption, is an expression that signifies an act that provides relief and comfort. The marriage of Ruth and Boaz is known as a levirate marriage, and this tradition has been passed down through generations until the New Testament era. Ruth was a woman from Moab. She was not a member of the nation of Israel, but Ruth received the gift of the opportunity to experience redemption. In this scientific paper, the researcher aims to explore the meaning of redemption contained in the Book of Ruth. The entire story of Ruth and Boaz's journey until its culmination, namely Ruth's redemption by Boaz, is a shadow image of God's plan and God's act of execution through the Person of Jesus Christ, namely the redemption of sinful humans that Jesus accomplished on the cross. This research uses a qualitative literature method. The qualitative literature study method used by this researcher is based entirely on literature review. Literature-based research is part of a research proposal, collecting data from sources such as books, articles, journals, online media, and other documents. In the New Testament, there are numerous verses explaining that the atonement for sins was performed only by Jesus Christ. Jesus' atonement is offered to all people, regardless of their nationality, just as Ruth received the gift of redemption from Boaz.